Relationship between vulvar symptoms and incidence of vulvar cancer in women referred to a rapid access clinic. Issue 3 (16th April 2019) - Wiggans, Alison; Coleridge, Sarah; Bryant, Andrew; Morrison, Jo
Abstract: Objective: We performed a study to estimate incidence of vulvar cancer in women with vulvar symptoms (irritation, pain, bleeding +/− presence of lesion) referred to a secondary care, rapid‐access clinic. Methods: Prospective data collection of all direct referrals from a primary to a secondary care gynecological oncology clinic from 2011 to 2016, for women with suspicious vulvar symptoms. Results: 32/393 (8.1%) women had vulvar cancer, and 24/393 (6.1%) had a premalignant lesion. Multivariate logistic regression showed that women referred without a specific lesion had considerably lower odds of a diagnosis of vulvar cancer than those with a lesion (OR=0.11, 95% CI: 0.03–0.49). In total, 30/234 (12.8%) women with a vulvar lesion (mass or ulcer), had vulvar cancer, compared with 2/159 (1.3%) of those referred without a lesion (these patients had vulvar irritation and bleeding but had a visible lesion on examination). None of the 140 women with irritation alone, in the absence of a visible lesion or bleeding, had pre‐invasive disease or cancer. Conclusion: Presence of a vulvar lesion, especially if painful/bleeding, has a high positive predictive value for vulvar cancer and 12.8% of women presenting with any vulvar lesion to secondary care had cancer. Abstract : 14% of women referred to a secondary care fast‐track clinic with vulvar symptoms had cancer or pre‐cancer. All those with cancer had a visible lesion.